Drámai szerkezetű regények Kemény Zsigmond írásművészetében: (Gyulai Pál; Özvegy és leánya) - Gönczy, Monika (Studia Litteraria, 2014)
The oeuvre of Zsigmond Kemény is confronted with several dilemmas of genre theory and practice when talking about the emergence of mixed genres, the growing “trend” of the novel, the artistic transmutation of aesthetically valued prose, and the changing tendencies of performing arts that reflect back upon stage writing which subvert the traditional hierarchy of genres. He recognizes that the precision of the novel can bear artistic values that create a possibility to preserve genre patterns and transfer certain genre functions. He makes it a writer’s program – using Kemény’s terminus technicus – to create the “dramatically structured novel”, setting out to rescue the aesthetic values of a deteriorating genre/form, while he is trying to create/stabilize a place in high poetry for a rising genre/form. At the same time, he is also undertaking an act of reception aesthetics and reading sociology by leading the receiver with a preference for reading novels who is becoming affected by the influences of performing arts back to reading drama. In the rich and continuous Kemény reception, the essay is targeting a not uncommon field. The new aspects of the text will examine two novels of Kemény (Pál Gyulai; The Widow and Her Daughter) and some critical works that were written between them (which is rather a long decade in the writer’s activity: 1845-1857) as the accomplished practice of the writer’s genre experiments.